ANALISIS GAYA KEPEMIMPINAN CAMAT PADA KANTOR CAMAT BUKAL KABUPATEN BUOL - Sondeng, Ahmad (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
The aim of this research is to analyze factors that influence employee performance. The research method used is a quantitative research method using descriptive analysis, using population and samples, research procedures using observation, interviews and questionnaires. The research results show that the leadership style applied by the sub-district head is a democratic style, a charismatic style and a paternalistic style. With these three types of leadership, you can easily provide role models, provide motivation and can improve the performance of employees at the Bukal District Head Office, Buol Regency.